2016
DOI: 10.12968/bjon.2016.25.4.212
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a nurse mentor preparation programme

Abstract: Following the introduction of a regional nurse mentor preparation programme, research was undertaken within a health and social care trust to explore both the trainee mentors' and their supervisors' perception of this new programme. A qualitative study involving focus groups was undertaken. The focus groups comprised a total of twelve participants including five trainee mentors and seven supervisors (experienced mentors) who had recently completed a mentor preparation programme. Data were analysed using Braun … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In addition, we sought to understand nurses" roles within the care homes, experience of previous training and gaps in knowledge. Focus group interviews were identified as the most suitable methodology as they enable insight into collective views and a range of viewpoints (Lawrence 2013) and facilitate reflective discussion (Gray and Brown 2016). Focus groups interviews have been successfully used to develop educational programmes (Barnack-Tavlaris 2013).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we sought to understand nurses" roles within the care homes, experience of previous training and gaps in knowledge. Focus group interviews were identified as the most suitable methodology as they enable insight into collective views and a range of viewpoints (Lawrence 2013) and facilitate reflective discussion (Gray and Brown 2016). Focus groups interviews have been successfully used to develop educational programmes (Barnack-Tavlaris 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Success is largely assumed rather than demonstrated. Huybrecht et al [23], Gopee [24], Eby et al [27], Paglis et al [29], Tonidandel, Avery and Phillips [30], and more recently Williams et al [31] and Gray and Brown [32], indicate that there is little evidence to suggest that mentoring adds value to outcomes or indeed to improving quality and safety through clinical governance. However, Snowden and Hardy [26] and Snowden [28] allude to the potential benefits of mentorship on academic performance and learning for mentees and mentors in health and social welfare, suggesting that mentorship can enhance performance.…”
Section: Characteristics Of Mentoring In Supporting the Application Omentioning
confidence: 99%
“…A recent study by Gray and Brown (2016) identified the emotional impact of the role which they described as the "personal investment" required. Participants in their study also described the tensions within the role in terms of balancing the commitment to both patient care and the student and coping with failing students.…”
Section: Mentors and Emotional Labourmentioning
confidence: 99%
“…The literature also identifies that senior nurses have a potential role to play in developing a favourable, positive learning culture for effective mentorship so that mentors feel well supported and able to undertake their roles (Black et al 2014, Gray andBrown 2016). In particular, senior nurses appear to be well placed to provide support for new mentors in the early stages of their mentorship development, in order to facilitate the application into practice of the knowledge and skills gained during mentor preparation programmes (Black et al, 2014).…”
Section: Current Sources Of Support For Mentorsmentioning
confidence: 99%